Use of a benzyl ether as a traceless hydrogen donor in the anti-Markovnikov hydrofunctionalization of alkenes with xanthates - Hayashi, Hirohito (2022)
A new protocol for the anti-Markovnikov hydrofunctionalization of alkenyl alcohol O-Bn ethers was developed using xanthates as functionalizing agents in the presence of lauroyl peroxide as a radical initiator and a stoichiometric oxidant. The benzyl group serves as a traceless hydrogen donor in the remote radical hydrogen atom transfer event during the process.